(untitled) (Journal of Vishwa Adarsha College, 2025)
Sustainable sanitation and hygiene are essential for public health, especially in rural areas of low-income countries like Nepal, where open defecation, poor waste management, and unsafe water use remain persistent challenges. Although Nepal has made commendable progress in improving sanitation coverage, ensuring long-term behavioral change and sustainability of hygiene practices continues to be a significant concern. This study assesses the impact of sustainable sanitation and hygiene interventions on household behaviors in Bheriganga Municipality, Surkhet. It particularly focuses on key hygiene practices, including hand washing, toilet usage, safe water handling, and waste disposal methods. A quantitative cross-sectional survey was conducted among selected households using structured questionnaires and relevant municipal records. The research employed a comparative approach to evaluate changes in hygiene behaviors before and after the implementation of the Sustainable Sanitation and Hygiene for All (SSH4A) program. The findings reveal notable improvements in various hygiene indicators, suggesting that the intervention effectively influenced household behavior. The study highlights that behavior-focused, community-driven WASH (Water, Sanitation, and Hygiene) programs can yield lasting health and environmental benefits. Overall, the SSH4A intervention resulted in sustainable improvements in rural sanitation practices, transforming Hariyali Tole into a model community. These results provide practical insights and policy implications for achieving broader national and global sanitation and hygiene goals.